Створення тонкоплівкової композиції для нової конструкції сонячного елементу з кестеритним базовим шаром - Клочко, Наталя Петрівна; Хрипунов, Геннадій Семенович; Лук'янова, Олександра Віталіївна; Копач, Володимир Романович; Волкова, Неоніла Дмитрієвна; Корсун, Валерія Евгеніївна; Любов, Віктор Миколаєвич; Кіріченко, Михайло Валерійович (Національний технічний університет "Харківський політехнічний інститут", 2016)
Створено тонкоплівкову композицію для нової конструкції сонячного елементу з кестеритним базовим шаром шляхом застосування двох недорогих і придатних для широкомасштабного виробництва рідиннофазних методів, а саме електроосадження і методу послідовної абсорбції і реакції іонних шарів. Вивчено структуру і оптичні властивості окремих шарів, досліджено електричні властивості гетероструктури Mo/р-Cu₂ZnSnS₄/n-ZnS/Al.

Development of physical and technological conditions of thin film ZnS/Cu₂ZnSnS₄ heterostructure fabrication for kesterite solar cells. Methodology. For ZnS/Cu₂ZnSnS₄ synthesis we used two inexpensive and suitable for large-scale production liquid-phase methods, namely electrodeposition with sulfurization (E+S) and successive ionic layer adsorption and reaction (SILAR) method. Main kesterite layers were obtained by E+S method using Cu/Sn/Zn metal precursors. SILAR was utilized to deposit nanograin kesterite and ZnS films on the Mo/Cu₂ZnSnS₄ surfaces as well as on glass substrates for investigation of their optical and structural properties. The desired thickness of kesterite or ZnS films was obtained by repeating SILAR cycles. Before applying ZnS layer ion etching of kesterite surface was made. Results. The study of crystal structure of samples fabricated by E+S method has shown that this layer is polycrystalline, single-phase and consists of kesterite Cu2ZnSnS4 with average size of crystal grains 73 nm. SILAR kesterite films were Xray amorphous with less than 3 nm crystallite size and had a direct optical bandgap Eg ≈ 1,7 eV, which is 0,2 eV higher than the Eg value of main Cu₂ZnSnS₄. The measurements by the hot probe showed that all kesterite layers have p-type conductivity. SILAR n-type ZnS layers were nanocrystalline as well. As a result, usage of such layers according to the dark I–U characteristics allowed creating Mo/p-Cu₂ZnSnS₄/n-ZnS/Al heterojunctions with rectifying barrier. Originality. The offered design of thin film composition can be used for kesterite solar cell fabrication on an industrial scale. Practical value. By kesterite ion etching process refinement diode and electronic parameters of n-ZnS/p-Cu₂ZnSnS₄ heterojunctions can be improved.
Creation of thin film composition for a new design of solar cells with kesterite base layer
Keywords: геліоенергетика; вольт-амперні характеристики; електрохімічне осадження; кестерит; хімічні реакції; thin film solar cell; kesterite; current-voltage characteristics